Path analysis of “new” humic acid derived from water hyacinth on phosphorus dynamics in P-deficient Inceptisols and chili response under intensive cultivation - Sofyan, Emma Trinurani; Hermawan, Mega Kartika; Sudirja, Rija; Nurbaity, Anne; Fitriatin, Betty Natalie; Mulyani, Oviyanti; Setiawati, Mieke Rochimi; Djuansah, Muhamad Rahman (Journal of Degraded and Mining Lands Management, 2026)
Phosphorus (P) deficiency in intensively cultivated Inceptisols is a persistent problem, not only because of low P reserves but also because of ongoing soil degradation, which reduces fertilizer use efficiency and is characteristic of degraded soils. This study aimed to develop a “new” humic acid from water hyacinth biomass (WHL) through accelerated aerobic decomposition using lignocellulolytic microorganisms and to evaluate its effectiveness in improving soil P dynamics and chili growth responses. The experiment was conducted on P-deficient Inceptisols of the Jatinangor series characterized by low P availability and high metal content. Water hyacinth collected from local reservoirs and rivers was aerobically decomposed with selected microbial starters to enhance humification. WHL was applied in combination with inorganic P fertilizer (SP-36), and its effects on soil P availability, phosphorus dynamics, and chili pepper growth and yield were evaluated using path analysis. The results showed that WHL significantly improved P dynamics mainly through an indirect mechanism involving increased P availability and reduced P fixation, thereby improving chili growth and yield. Application of WHL at a rate of 30 kg ha?¹ combined with SP-36 at a rate of 250 kg ha?¹ produced responses comparable to those obtained with commercial humic acid. These findings indicate that WHL has strong potential as a renewable and cost-effective alternative source of humic acid to improve phosphorus efficiency, restore soil chemical function, and reduce dependence on inorganic P fertilizers in degraded Inceptisols under intensive cultivation.